Action of painkillers with caffeine and pain crises - de Freitas, Isabela Ferreira; Pietro, Luciana (Brazilian Journal of Health and Biomedical Sciences, 2022)
Pain is considered to be one of the main consequences of trauma and migraines, and is characterized by moderate to severe headache attacks that affect more than one billion people worldwide. Its treatment is mainly done by over-the-counter drugs, most of which are combined with caffeine. Objective: To analyze whether analgesics combined with caffeine are more effective for the treatment of acute and/or chronic pain than analgesics not combined with caffeine. Methods: A systematic review was carried out based on scientific articles published in the following databases: SCIELO, PubMed and Science Direct. We analyzed 15 original articles with clinical trials and controlled trials that evaluated the efficacy of analgesics combined with caffeine and were published between 2010 and 2020. Results:The 15 studies under analysis evaluated a total of 5,030 patients. Of these studies, ten concluded that analgesics associated with caffeine are more effective for the treatment of acute and/or chronic pain;four concluded that the two types of analgesics are equally effective; and one study concluded that the non-combined analgesic is more effective. Conclusion: analgesics combined with caffeine are more effective for the treatment of acute and/or chronic pain crises, since they promote faster pain relief and achieve a complete cessation of pain. Caffeine is believed to act by inhibiting cyclooxygenase at some sites and by blocking central and peripheral adenosine receptors.